Rapid transient production in plants by replicating and non-replicating vectors yields high quality functional anti-HIV antibody. - Frank Sainsbury; Markus Sack; Johannes Stadlmann; Heribert Quendler; Rainer Fischer; George P Lomonossoff (PLoS ONE)
Background The capacity of plants and plant cells to produce large amounts of recombinant protein has been well established. Due to advantages in terms of speed and yield, attention has recently turned towards the use of transient expression systems, including viral vectors, to produce proteins of pharmaceutical interest in plants. However, the effects of such high level expression from viral vectors and concomitant effects on host cells may affect the quality of the recombinant product. Methodology/principal findings To assess the quality of antibodies transiently expressed to high levels in plants, we have expressed and characterised the human anti-HIV monoclonal antibody, 2G12, using both replicating and non-replicating systems based on deleted versions of Cowpea mosaic virus (CPMV) RNA-2. The highest yield (approximately 100 mg/kg wet weight leaf tissue) of affinity purified 2G12 was obtained when the non-replicating CPMV-HT system was used and the antibody was retained in the endoplasmic reticulum (ER). Glycan analysis by mass-spectrometry showed that the glycosylation pattern was determined exclusively by whether the antibody was retained in the ER and did not depend on whether a replicating or non-replicating system was used. Characterisation of the binding and neutralisation properties of all the purified 2G12 variants from plants showed that these were generally similar to those of the Chinese hamster ovary (CHO) cell-produced 2G12. Conclusions Overall, the results demonstrate that replicating and non-replicating CPMV-based vectors are able to direct the production of a recombinant IgG similar in activity to the CHO-produced control. Thus, a complex recombinant protein was produced with no apparent effect on its biochemical properties using either high-level expression or viral replication. The speed with which a recombinant pharmaceutical with excellent biochemical characteristics can be produced transiently in plants makes CPMV-based expression vectors an attractive option for biopharmaceutical development and production.